Insights into the Galapagos plume from uranium-series isotopes of recently erupted basalts - Handley, H; Turner, S; Berlo, K; Beier, C; Saal, A (2011)
Uranium-series isotopes (238U-230Th- 226Ra-210Pb), major element, trace element, and Sr-Nd isotopic data are presented for recent (<60 years old) Galpagos archipelago basalts. Volcanic rocks from all centers studied (Fernandina, Cerro Azul, Sierra Negra, and Wolf Volcano) display 230Th excesses (4%-15%) and steep rare earth element (REE) patterns indicative of residual garnet during partial melting of their mantle source. Rare earth element modeling suggests that only a few percent of garnet is involved. Correlations between (238U/ 232Th), radiogenic isotopes and Nb/Zr ratio suggest that the U/Th ratio of these Galpagos volcanic rocks is primarily controlled by geochemical source variations and not fractionation during partial melting. The lowest (230Th/238U) ratio is not observed at Fernandina (the supposed center of the plume) but at the more geochemically "depleted" Wolf Volcano, further to the north. Small radium excesses are observed for all samples with (226Ra/230Th) ranging from 1.107 to 1.614. The 226Ra-230Th disequilibria do not correlate with other uranium-series parent-daughter nuclide pairs or geochemical data, suggesting modification at shallow levels on timescales relevant to the half-life of 226Ra (1600 years). The combination of 226Ra and 210Pb excesses is inconsistent with interaction of magma with cumulate material unless decoupling of 210Pb (or an intermediate daughter, such as 222Rn) occurs prior to modification of Ra-Th disequilibria. An intriguing correlation of (210Pb/ 226Ra)0 with Nb/Zr and radiogenic isotopes requires further investigation but suggests possible control via magmatic degassing and accumulation that may somehow be related to source heterogeneities. Copyright 2011 by the American Geophysical Union.